2013
DOI: 10.1002/ps.3626
|View full text |Cite
|
Sign up to set email alerts
|

Electrical penetration graph studies to investigate the effects of cyantraniliprole on feeding behavior of Myzus persicae (Hemiptera: Aphididae) on Capsicum annuum

Abstract: These findings document significant effects of cyantraniliprole on feeding by Myzus persicae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Interactions between the stylet penetration activities of the sucking insects and the host plants play an important role in determining the disease transmission efficiency. The electrical penetration graph (EPG) technique has been used to study insect feeding behaviour linked to the transmission process of pathogens (Tjallingii, 1985;Jacobson & Kennedy, 2014;Luo et al, 2015;Wu et al, 2016). In our previous study, we described six EPG waveforms correlated with the stylet penetration activities during probing by the SCWL phytoplasma vector M. hiroglyphicus, of which the waveforms C and D were linked to acquisition and inoculation, respectively (Roddee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between the stylet penetration activities of the sucking insects and the host plants play an important role in determining the disease transmission efficiency. The electrical penetration graph (EPG) technique has been used to study insect feeding behaviour linked to the transmission process of pathogens (Tjallingii, 1985;Jacobson & Kennedy, 2014;Luo et al, 2015;Wu et al, 2016). In our previous study, we described six EPG waveforms correlated with the stylet penetration activities during probing by the SCWL phytoplasma vector M. hiroglyphicus, of which the waveforms C and D were linked to acquisition and inoculation, respectively (Roddee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The electrical penetration graph (EPG) technique clearly shows the locations and activities of aphid stylets in real time, including probing, phloem salivation and passive uptake of phloem sap . The feeding behaviour of pea aphids on M. truncatula with and without nitrogen fertilization was studied as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted using water sensitive paper to determine the whitefly adult feeding, when insects were exposed to insecticide-treated and untreated plants [35]. Other studies have also shown that cyantraniliprole reduces feeding of thrips [24] and aphids [25].…”
Section: Discussionmentioning
confidence: 99%